Bank Credit and Private Sector Performance in Nigeria: Do Remittances Really Matter? - Igbinedion, Sunday Osahon (Acta Universitatis Danubius. Œconomica, 2023)
The pivotal role of the private sector as economic driver in promoting economic performance among nations has been acknowledged in economic literature. And, one major constraint facing the private sector in promoting private sector growth is the paucity and unaffordability of funds (bank credit) for profitable investment. In this regard, migrants’ remittances have emerged as one of the perspective avenues of funds to complement the shortfall in domestic credits to the private sector. Yet, there is the on-going debate over the nexus between remittances and private sector growth, given that, in theory, remittances are extensively utilized for consumption and investment. This study re-examines this debate within the Nigerian context. Specifically, this study investigates the impact of bank credit and remittances on private sector performance within the ARDL and Bound test framework in Nigeria utilizing annual data spanning 1981 to 2021. The result revealed that both bank credit and remittances inflow have positive and statistically significant impact on private sector performance. However, in the long-run, only bank credit matter while remittances impacted negatively on private sector performance. This development calls for the strengthening of remittances channels in order to promote private sector performance in the short-run as well as in the long-run.